Dolutegravir Plus Lamivudine as Initial Therapy for HIV-1 Infected and ARV-naïve Patients in West China, 24-Weeks Results of a Preliminary Real-world Study - Hui, Xia; Gan, Xinrong; Li, Qian; Sun, Wei (Current HIV Research, 2022)
Introduction: This preliminary real-world study (RWS) was designed to evaluate the antiviral efficacy, safety, and feasibility of the 2-drug regimen (2DR), dolutegravir plus lamivudine as the initial antiretroviral therapy (ART) among antiretroviral (ARV)-naïve adults with HIV-1 in West China. Methods: This RWS included the treatment of treatment-naïve adults applying 2DR of dolutegravir 50 mg once daily (QD) plus lamivudine 300mg QD with negative HBsAg from one single center of People’s Hospital of Chongqing Banan District in West China. Viral load (VL), CD4+ T-cell count, and laboratory indicators were collected at baseline; weeks 4, 12, and 24, and thereafter every 24 weeks up to 144 weeks. The primary endpoint was the proportion of patients with HIV-1 RNA <50 copies/mL at week 24. Results: A total of 54 ART-naïve patients were treated with the 2-drug regimen of DTG plus 3TC and were enrolled in this study since April 1st, 2020. Twenty-one patients received 24-week VL tests at screening as required by inclusion criteria. Median HIV-1 RNA at entry was 95,700 copies/ mL (interquartile range (IQR): 28,300-310,000) and the median baseline CD4+ cell count was 249 per cubic millimetre(IQR: 118-310). At week 24, 15 (71.4%) of 21 participants achieved virological success, defined as HIV-1 RNA < 50 copies/mL, while 10 (90.9%) of 11 participants with a baseline HIV-1 RNA < 100,000 copies/mL achieved virological success compared with 5 (50%) of 10 participants with a baseline HIV-1 RNA ≥100,000 copies/mL [Relative Risk (RR) 1.818; 95% CI 1.018-1.927]. In participants with CD4+ cell counts ≥ 200 cells/mm3, 9 (75%) of 12 participants achieved virological success compared with 6 (66.7%) of 9 participants with baseline CD4+ cell count < 200 cells/mm3 achieved it (RR 1.124; 95% CI 0.641-1.970). No major tolerability/toxicity issues were observed. Conclusion: This real-world study suggested that the 2-drug regimen of DTG plus 3TC could be considered as an alternative for ART-naïve patients in West China, especially with HIV-1 RNA less than 100,000 copies/mL at baseline, regarding the limits of viral load test frequency and the absence of HIV genotypic testing of viral resistance.
Keywords: HIV